Effectiveness of International Legal Instruments in Preventing and Eradicating Human Trafficking: Palermo Protocol Implementation Study - Maharani, Natalia; Widagdo, Setyo; Istiqomah, Milda; Puspitawati, Dhiana; Anditya, Ariesta Wibisono (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2026)
Human trafficking is a complex, transnational crime intrinsically linked to human rights violations, requiring a holistic legal response at both international and domestic levels. The Palermo Protocol has served as an essential international legal instrument; yet, it continues to face numerous problems. This research aims to assess the effectiveness of the Palermo Protocol as an international legislative instrument for the prevention and eradication of human trafficking by analyzing its implementation in Indonesia and the Philippines. The research methodology utilized is normative juridical, integrating legislative, conceptual, and comparative legal frameworks. The results indicate that the Palermo Protocol is relatively effective in promoting legal harmonization and establishing institutional frameworks in ratifying nations; yet, it has not completely bridged the gap between international standards and their practical implementation. In Indonesia, fragmented authority, the limited competence of law enforcement officials, and an inadequate integrated data system present substantial obstacles to victim identification and protection. The Philippines, on the other hand, has a more cohesive legal and institutional framework that makes it easier to adopt international norms. However, it still struggles to do so because it relies on external resources and faces structural problems such as poverty, labor migration, and gender inequality. This study finds that the Palermo Protocol works well as a global standard, but it hasn't done much to lower the number of people who are trafficked. Consequently, improving the protocol's effectiveness requires evolving from a passive, normative framework into an active, accountable, victim-centered legal system harmonized with extensive socio-economic policies.